Chapter 9. Synthetic probes for polyketide and nonribosomal peptide biosynthetic enzymes - Meier, Jordan L; Burkart, Michael D (Methods in enzymology, 2009)
Polyketides and nonribosomal peptides constitute two classes of small molecule natural products that are well-known for their ability to impact important biological processes in a multitude of ways. The modular biosynthetic enzymes responsible for production of these compounds (PKS and NRPS enzymes) have been the subject of extensive genetic, biochemical, and structural characterization, in part due to the potential utility their successful reengineering may have for the production of new therapeutics. In this chapter, we provide background as well as specific techniques in which synthetically produced small molecule probes have been applied to help better understand the mechanism and structure of PKS and NRPS biosynthetic pathways, as well as to help streamline their discovery process. The continued development and application of these methods has the potential to greatly complement our current approaches to the study of natural product biosynthesis.